Efficacy and Safety of intralesional injection of verapamil in treatment of keloids - Haidar, Ghoufran SaifAlden; Khaddam, Jamal (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to evaluate the efficacy of intralesional verapamil injection in treating keloids. In addition to, assessment of side effects of the therapy. Patients and Methods: A Prospective study (Before& After) conducted for the period one year (April 2020- April 2021) at Tishreen University Hospital in Lattakia- Syria. 30 patients with keloids who received treatment with verapamil were included in the study. Results: The mean age was 22±6.3 years, 66.7% of patients were females. Most common sites of keloids involvement were shoulders (46.7%), and acne vulgaris was the most frequently etiology (40%). A statistically significantly reduction in the means of: Vancouver Scar Scale VSS 4.66±1.9 (day 21 of last treatment) vs. 7.06±1.8 (Day 0), p: 0.0001), height (1.16±0.6 vs. 2.23±0.6, p: 0.001), and pliability (1.33±0.9 vs. 2.60±0.6, p: 0.003), without recurrence of keloids at the day 90 of the last treatments. Burning pain was the most side effect frequently seen (98%).There was no significant relationship between clinical improvement and each of the following: duration of disease and age of the patient (p>0.05). Conclusion: Verapamil has significant therapeutic effects in decreasing the height of the lesion, improving pliability without recurrence of lesions or serious adverse effects, thus, it could be a safe choice in treatment of keloids.